2009
DOI: 10.1007/s12272-009-1709-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of caspase-9 and poly(ADP-ribose) polymerase inhibitors on ischemia-reperfusion-induced myocardial injury

Abstract: The present study was designed to investigate the cardio-protective effect of Ac-LEDH-cmk a selective caspase-9 inhibitor and 5-aminoisoquinolinone a selective Poly (ADP-ribose) polymerase inhibitor on ischemia and reperfusion induced apoptotic and necrotic cell death in rats. Isolated rat hearts were exposed to 30 minutes of global ischemia followed by 120 minutes of reperfusion using Langendorff's apparatus. Myocardial injury was assessed in the terms of infarct size, release of lactate dehydrogenase, creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It is involved in a wide range of physiological processes including DNA repair, gene transcription and genomic stability maintenance, cell cycle progression, and apoptosis [18]. Several studies showed that inhibition of PARP has a protective effect on various organs during I/R [12][13][14]19]. In this study, increased concentration of MDA, an index of oxidative stress, and activation of PARP were strongly associated with increased apoptosis in the bladder after AUR and subsequent empting.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is involved in a wide range of physiological processes including DNA repair, gene transcription and genomic stability maintenance, cell cycle progression, and apoptosis [18]. Several studies showed that inhibition of PARP has a protective effect on various organs during I/R [12][13][14]19]. In this study, increased concentration of MDA, an index of oxidative stress, and activation of PARP were strongly associated with increased apoptosis in the bladder after AUR and subsequent empting.…”
Section: Discussionsupporting
confidence: 51%
“…This is the main limitation of the present study. However, several recent reports have indicated that AUR not only induces bladder damage, but also induces functional and structural impairment of the heart, liver, and kidney [35][36][37] and inhibition of PARP-attenuated damage to several organs such as brain, kidney, liver, and heart under I/R conditions [12][13][14]19]. Considering these reports, we presume that inhibition of PARP may have beneficial effects on attenuating damage to other organs aside from the bladder.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies have revealed that caspase-3 is the main apoptotic effect factor and the most important protease involved in cell apoptosis [32], while caspase-9 is required in most scenarios of apoptotic cell death. Numerous studies have demonstrated that caspase-9 [33] and caspase-3 [34] participate in myocardial infarction progression, and inhibition of caspase-9 [35] and caspase-3 [36] can significantly reduce ischemia-induced myocardial apoptosis with cardiac function improved. Our preliminary experiment showed that caspase-9 was activated after CME and that using caspase-9-specific inhibitor could significantly decrease myocardial apoptosis and improve cardiac function following CME [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also examined the activity of poly (ADP-ribose) polymerase (PARP), because recent studies have demonstrated that increase in ROS following I/R injury increases PARP activity and causes damage in several organs, such as brain, kidney and the heart (12-14). …”
Section: Introductionmentioning
confidence: 99%